2000
DOI: 10.1093/jn/130.12.2889
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term High Protein Intake Does Not Increase Oxidative Stress in Rats

Abstract: The maximum dietary protein intake that does not cause adverse effects in a healthy population is uncertain. We tested whether a high protein intake enhances oxidative stress. Adult rats were adapted to different casein-based diets containing either an adequate (13.8%; AP), medium (25.7%; MP), or high (51.3%; HP) level of crude protein; a fourth group received a HP diet but no RRR-alpha-tocopherol acetate (HP-toc). After 15 wk of feeding, plasma protein carbonyl concentration, liver lipid peroxide levels [thio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 43 publications
4
42
1
1
Order By: Relevance
“…According to those authors, high dietary protein levels can reduce oxidative stress. On the contrary, Petzke et al (2000) observed that long-term intake of high-protein diets did not lead to oxidative stress in adult rats. Celi and Robinson (2010) found that TAC is affected by dietary treatment with yerba mate (Ilex paraguariensis) in dairy calves, most likely because of the high polyphenol content of this herb.…”
Section: Plasma Oxidant-antioxidant Contentmentioning
confidence: 90%
“…According to those authors, high dietary protein levels can reduce oxidative stress. On the contrary, Petzke et al (2000) observed that long-term intake of high-protein diets did not lead to oxidative stress in adult rats. Celi and Robinson (2010) found that TAC is affected by dietary treatment with yerba mate (Ilex paraguariensis) in dairy calves, most likely because of the high polyphenol content of this herb.…”
Section: Plasma Oxidant-antioxidant Contentmentioning
confidence: 90%
“…13 C]KIC and unlabeled KIC corrected for baseline were used for calibration (41). 13 C enrichment in breath samples was analyzed by IRMS (Breath, Finnigan).…”
Section: Volunteersmentioning
confidence: 99%
“…Indeed, it has now clearly been shown that Savary-Auzeloux, Durand, Gruffat, Bauchart and Ortigues-Marty a drastic (a reduction to 60% of the ad libitum food intake level) or a long-lasting (several months) food restriction decreased the carbonyl content in human plasma (Dandona et al, 2001) and in the muscles or in the liver of rodents (Nagai et al, 2000;Pamplona et al, 2002). By contrast, other more specific alterations of the diet composition such as high protein content in the diet of rats (Petzke et al, 2000) or supplementation with eicopentaenoic acid and decosahexaenoic acid (Wander and Du, 2000) in humans had no effect on plasma protein carbonyls. In cattle finished on pasture (rich in polyunsaturated fatty acids) and compared with animals fed high concentrate diets, there was a similar (Mercier et al, 2004) or an increased (SavaryAuzeloux et al, 2001) content in protein carbonyls in some muscles.…”
Section: Resultsmentioning
confidence: 84%